2012
DOI: 10.3171/2011.12.focus11315
|View full text |Cite
|
Sign up to set email alerts
|

Inequities in access to pediatric epilepsy surgery: a bioethical framework

Abstract: Epilepsy is a common childhood condition associated with a considerable medical and psychosocial burden. Children in whom medical treatment fails to reduce seizure burden represent an especially vulnerable patient population because prolonged, uncontrolled seizures are associated with poor developmental and neurocognitive outcomes. Surgical treatment in the form of cortical resection, functional disconnection, or neuromodulation may alleviate or significantly reduce the disease burden for a subset of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Access to epilepsy surgery remains a considerable challenge in contemporary healthcare systems 5 . The average delay between a diagnosis of medically intractable epilepsy and referral for surgical consideration and surgery can be as long as 15-22 years 6,7 .…”
Section: Original Articlementioning
confidence: 99%
“…Access to epilepsy surgery remains a considerable challenge in contemporary healthcare systems 5 . The average delay between a diagnosis of medically intractable epilepsy and referral for surgical consideration and surgery can be as long as 15-22 years 6,7 .…”
Section: Original Articlementioning
confidence: 99%
“…This could make a case that epilepsy surgery may have been unfairly neglected compared to surgical treatment of other public health conditions [197]. Health care providers also have an ethical obligation to identify and facilitate access to epilepsy surgery for these vulnerable subgroups [198]. Whether minimally invasive surgeries may be a cost effective or efficacious option is an ongoing discussion, as subjects may be more willing to undergo minimally-invasive procedures due to lower perceived risks [199].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously explored this topic as it relates to the use of palliative surgical procedures to achieve a reduction in seizure frequency in children with medically intractable epilepsy 37 . As such children have a lower margins of improvements in their quality of life, they risk having a lower priority placed on treatments that can improve their lives, the socalled "double jeopardy" [38][39][40] . It has been suggested that implementation of A4R applies a human rights approach to health 41 , which would take into consideration the respective benefit to marginalized or vulnerable patient groups.…”
Section: Discussionmentioning
confidence: 99%